Small Cationic Peptides: Influence of Charge on Their Antimicrobial Activity - Lopez Cascales, Jose Javier (2018)
The first stage of the action mechanism of small cationic peptides with antimicrobial activity is ruled by electrostatic interactions between the peptide and the pathogen cell membrane. Thus, an increase in its activity could be expected with an increase in the positive charge on the peptide. By contrast, the opposite behavior has been observed when the charge increases to reach a critical value, beyond which the activity falls. This work studies the perturbation effects in a cell membrane model for two small cationic peptides with similar length and morphology but with different cationic charges. The synthesis and antibacterial activity of the two peptides used in this study are described. The thermodynamic study associated with the insertion of these peptides into the membrane and the perturbing effects on the bilayer structure provide valuable insights into the molecular action mechanism associated with the charge of these small cationic peptides.